Effect of Meloidogyne incognita and M. javanica on Leaf Water Potential and Water Use of Tobacco - Rahi, G S (Journal of nematology, 1988)
Greenhouse lysimeter and field microplot tests were conducted to evaluate the effects of Meloidogyne incognita and M. javanica on plant water relations and growth performance of NC 2326 flue-cured tobacco. In the greenhouse, afternoon leaf water potential values at 8-11 weeks after transplanting were lower by as much as 0.22 MPa in plants infected with either nematode than in the control plants. From 11 to 22 weeks, leaf water potential values were similar in all treatments. Over the course of the 22-week experiment, all infected plants showed similar evapotranspiration patterns, and plants in these treatments used 87-88% of the water utilized by noninfected plants. Biomass production from nematode-infected plants, however, was only about 50% of the biomass of control plants. The field microplot study showed water use patterns similar to those in the lysimeter study